The Structure of Information Support System of the Enterprise Production Work - A. M. Bochkarev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article defines the meaning of the idea 'the information support system of production activity'. In comparison with the academic approach describing information support as a totality of system elements it was shown that the interaction of elements' totality aims at performing key functions of information support (collection, processing, storage, revision, renewal of information, preparation for use) and attaining the principle goal of timely delivery of objective, trustworthy, complete information about the condition of enterprise production work and its external environment. Specified and amended definition reveals the essence of the information support system in organization of production work and management at the enterprise. On the basis of this definition key elements were identified and a structural model of the information support system was developed. The author worked out methodology for assessing the efficiency of information support of enterprise production work, whose specific features includes 4 criteria: availability of key elements of the system, sufficiency, accessibility and demand. By results of assessment 3 levels of the system development can be identified: high, medium and low. Assessing the system of information support can help find bottle necks and show key lines in developing the system. Academic novelty of the research implies the development of theoretical-methodological provisions and working out a set of practical recommendations aimed at upgrading the information support system of enterprise production work.